Resolving resistance adaptations: an integrated, evolutionary perspective across taxonomic borders - Nogueira Alves, Andre; Elgar, Mark; Wedell, Nina (Frontiers in Ecology and Evolution, 2026)
Resistance to xenobiotic compounds—including insecticides, herbicides, antibiotics, fungicides, and chemotherapies — is a pervasive and intensifying problem across agriculture, medicine, and public health. Billions are invested each year into creating new compounds to combat pests, pathogens, and cancer cells, yet resistance evolves swiftly and repeatedly. This recurring failure stems not from a lack of innovation but from a lack of integration. Current strategies are predominantly developed within disciplinary and taxonomic silos, and often ignore the evolutionary nature of resistance. This topic is extremely relevant and contemporary as the emergence of resistance is an evolutionary inevitability whenever a population is exposed to strong selection pressures such as xenobiotic compounds. Despite this, resistance management remains reactive and compound-specific, relying on successive chemical innovations rather than long-term strategies. In this piece, the authors argue that resistance is not a domain-specific phenomenon, but a general evolutionary process. Drawing together research across insects, bacteria, fungi, plants, and cancer biology, this Perspective outlines how comparative insights and integrative strategies can reshape the way we approach resistance in both agricultural and biomedical systems. To confront this pressing and pervasive issue — where evolution outpaces our interventions — we must adopt an integrative evolutionary perspective that is anticipatory, not reactive. Resistance to xenobiotics is a shared evolutionary outcome across life forms, and so too should be our approach to solving it. This Perspective will serve as a conceptual bridge for researchers across domains, encouraging coordinated, evolutionary-informed solutions to one of the most pressing challenges of our time.